2020
DOI: 10.3390/ma13041010
|View full text |Cite
|
Sign up to set email alerts
|

Free Vibration Analysis of Curved Laminated Composite Beams with Different Shapes, Lamination Schemes, and Boundary Conditions

Abstract: A general formulation is considered for the free vibration of curved laminated composite beams (CLCBs) with alterable curvatures and diverse boundary restraints. In accordance with higher-order shear deformation theory (HSDT), an improved variational approach is introduced for the numerical modeling. Besides, the multi-segment partitioning strategy is exploited for the derivation of motion equations, where the CLCBs are separated into several segments. Penalty parameters are considered to handle the arbitrary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Bolotin (1964) indicated that considering 2T= π/λ as period provides significant importance since the widths of the unstable regions are generally larger than those solved with period T = 2π/λ. Hence, performing a periodic solution considering the period as 2T on Equation (19) gives the eigenvalue problem of dynamic stability analysis as…”
Section: Figure 5: Transformation Of Local Coordinatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bolotin (1964) indicated that considering 2T= π/λ as period provides significant importance since the widths of the unstable regions are generally larger than those solved with period T = 2π/λ. Hence, performing a periodic solution considering the period as 2T on Equation (19) gives the eigenvalue problem of dynamic stability analysis as…”
Section: Figure 5: Transformation Of Local Coordinatesmentioning
confidence: 99%
“…They considered Hamilton's principle and first-order shear deformation theory to derive the governing equations of motions of the beam which is rested on Vlasov's foundation. Qin et al (2020) examined the vibration characteristics of the composite curved beams. For this purpose, they considered elliptical, parabolic, hyperbolic, and circular curved beams.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, elliptical, circular, and parabolic types of curves are considered. The elliptical, circular, and parabolic curves with the relevant geometrical parameters are given in Figure 4 ( Qin et al, 2020). The symbols given in Figure 4 are the drawing parameters of the curved geometries.…”
Section: Curvature Geometriesmentioning
confidence: 99%
“…The displacement field that characterizes the Third-order Shear Deformation Theory (TSDT), for instance, determines a quadratic profile of shear strains and stresses along the thickness [ 7 , 8 ], due to its cubic expansion in the thickness coordinate. Consequently, there is no need for the shear correction factor [ 9 , 10 , 11 , 12 ]. The importance of these cubic terms in the analysis of laminates has been recently highlighted in the paper by Petrolo and Carrera [ 13 ], in which the best theory diagrams for multilayered structures have been widely discussed.…”
Section: Introductionmentioning
confidence: 99%